Stem Cell–Based Therapies via Different Administration Route for Stroke: A Meta-analysis of Comparative Studies - Gabriella Jeanne Mulia; Novelia Anna; John Chung-Che Wu; Hon-Ping Ma; Yung-Hsiao Chiang; Ju-Chi Ou; Kai-Yun Chen (Cell Transplantation)
Stroke, a neurological condition from compromised cerebral blood perfusion, remains a major global cause of mortality and disability. Conventional therapies like tissue plasminogen activator are limited by narrow therapeutic windows and potential adverse effects, highlighting the urgency for novel treatments. Stem cell–based therapies, with their neuroprotective and regenerative properties, present a promising yet highly diverse alternative. By conducting literature search and data extraction from the PubMed, Embase, and Cochrane databases, this meta-analysis assessed the clinical efficacy and safety of stem cell–based therapies administered via intravenous (IV) and non-IV routes in 17 studies with stroke patients. Primary outcomes included the National Institute of Health Stroke Scale (NIHSS), Barthel Index (BI), and modified Rankin Scale (mRS), while secondary outcomes included mortality and adverse events. Results demonstrated significant improvements in NIHSS, BI, and mRS scores, particularly in non-IV groups within 6- and 12-month follow-ups, suggesting delayed but enhanced therapeutic efficacy. Mortality was reduced in both IV and non-IV groups, indicating treatment safety. Adverse events, categorized into neurological and systemic complications, showed no significant differences between intervention and control groups, further emphasizing the safety of stem cell therapies. Non-IV routes showed more long-term benefits, potentially due to enhanced cell delivery and integration. These findings demonstrate the potential of stem cell therapies to improve functional recovery and survival in stroke patients, regardless of administration route. However, the delayed response underscores the need for extended follow-up in clinical applications. Further research is required to standardize treatment protocols, optimize cell types and doses, and address patient-specific factors to integrate stem cell therapies into routine clinical practice.